Mexico : Review Under the Flexible Credit Line Arrangement-Press Release; and Staff Report. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2018)
Mexico's economy has exhibited resilience in the face of a complex external environment. The current administration has responded appropriately to the recent external shocks and demonstrated its commitment to macroeconomic stability. The incoming administration is committed to maintaining very strong policies and policy frameworks going forward. Nevertheless, Mexico's strong trade and financial links to the global economy, and in particular the United States, make it susceptible to changes in investor sentiment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet